PENGARUH PADAT PENEBARAN TERHADAP PERTAMBAHAN BERAT DAN PANJANG BADAN BELUT SAWAH (MONOPTERUS ALBUS) - KETUT ALIT, I GUSTI (Jurnal Biologi Udayana; Vol 13 No 1 (2009): JURNAL BIOLOGI, 2009)
This experiment performed to find out the effect of stocking density on body weight and body length of freshwater eel (Monopterus albus). In this experiment 160 individual freshwater eels that planted in 20 clay pots. Completely Randomized Design (CRD) with five treatments and four replicates applied in this experiment. The treatments of different stocking densities were 4 eels/pot, 6 eels/pot, 8 eels/pot, 10 eels/pot, 12 eels/pot. Significant gains were recorded on body weight (P 0,05) for different stocking densities.
Keywords: freshwater eel; stocking density; body weight; body length